Keunggulan Produk Iconic Isolating Sarung Samarinda - Herning Indriastuti; Syarifah Hudayah (University of Merdeka Malang, 2017)
This research examines whether marketing innovativeness (MI) enhance marketing performance (MP) and tries to solve the problems of research gap between marketing innovativeness and marketing performance. The sample are SME’s Saroong Samarinda indutries in East Borneo, Indonesia. The total data that can be further analysed are 235 respondents. Data analysing uses Structural Equation Modelling. The result showes that : 1) small companies in these market segments based regiocentric is likely have better marketing performance when they have the iconiq isolating advantages, 2) the marketing innovativeness has significant effect on iconiq isolating advantages, 3) iconiq isolating advantages is a mediator in the correlation of marketing innovativeness and marketing performance https://doi.org/10.26905/jmdk.v5i2.1740